Experimental study of combination emission gas and hot water from power plant for enhanced heavy oil recovery. (December 2020) - Han, Bingbing; Li, WenJun; Li, Meng; Liu, Lei; Song, Junfeng
Abstract: There are lots of emission gas and hot water generating from power generation system, which can be been utilization again to improve energy efficiency and reduce gas emission. For utilization of emission gas and hot water from power plant of oil flied, this paper analyzed and compared combination emission gas including CO2, flue gas, N 2 and Air co-injected with hot water flooding for heavy oil recovery. The experiments results indicate that different gases including CO2, N 2, Air and Flue gas co-injected with hot water can significantly improve recovery of reservoir, and CO2 co-injected with hot water has the beat recovery factor compared to the other gas co-injected for enhanced heavy oil recovery. By measuring the temperature field of reservoir, it finds that co-injected CO2 does not affect the heat effect of hot water.